La consommation collaborative aux États-Unis - Marie-Christine Pauwels (Revue LISA)
This article studies one of the most striking evolutions of the United States consumer society by focusing on the fast-growing sharing economy, also sometimes called collaborative consumption. Based on the premise that the overconsumption paradigm which is at the root of the current American capitalist system is wasteful and destructive, this new sharing model has been developing quickly online over the past decade. Multiple peer-to-peer networks and lending platforms enable users to exchange, swap, barter or share goods and services over the Internet, thus redefining the notion of ownership, material possession, and what Thornstein Veblen referred to as conspicuous consumption.